DISCREPANCY MANAJEMEN LAYANAN KONSELING INDIVIDUAL DI SEKOLAH MENENGAH ATAS - Rahmawati Rahmawati; Putri Inayah; Dyah Amelia Susanti; Nor Khofifatus Sholehah; Titin Indah Pratiwi; Bambang Dibyo Wiyono (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2026)
Guidance and Counseling (BK) management in schools plays a strategic role in student development, yet its implementation often faces obstacles in meeting the Operational Implementation Guidelines (POP) standards. This study aims to identify the discrepancy between the ideal POP BK standards and the actual implementation of individual counseling management at SMA Negeri 4 Surabaya. This study employed an evaluative approach using the Discrepancy Evaluation Model (DEM) to assess Planning, Organizing, Actuating, and Controlling (POAC) aspects. Data were collected via interviews, observations, and documentation to compare actual conditions with established standards. The results show that overall, individual counseling management complies with standards, but implementation is not yet comprehensive. Significant discrepancies were found in the counseling process, which lacked theoretical adherence, needs assessments limited to AKPD instruments, and outcome evaluation and follow-up restricted to monitoring without in-depth analysis. While service management is functional, strengthening counselors' professional competence and developing data-driven evaluation systems are necessary to optimize counseling effectiveness.